"EVALUATION OF THYROID STATUS IN NEWLY DIAGNOSED TREATMENT NAIVE WOMEN WITH POLYCYSTIC OVARIAN SYNDROME" - Dr Humairah Shafi; Dr Samia Mearaj; Dr Khalid Ahmad Bhat; Dr Shabir Ud din Lone; Dr. Nazir Ahmad Pala; Dr. Sabhiya Majid; Dr. Sheikh Imran Sayeed (Journal of Population Therapeutics and Clinical Pharmacology, 2024)
Polycystic ovarian syndrome (PCOS) is the most common endocrine disorder among women of reproductive age, with significant reproductive and metabolic implications, including links to insulin resistance, dyslipidemia, and cardiovascular risks. Recent studies indicate an association between PCOS and thyroid dysfunction, particularly autoimmune thyroid disease, highlighting the need for a better understanding of this relationship to improve patient management, especially in high-prevalence regions like Kashmir. This study aimed to evaluate thyroid function status in newly diagnosed PCOS patients and assess the prevalence of autoimmune thyroid disease in this population. Conducted as a cross-sectional study, it included 90 newly diagnosed, treatment-naive PCOS patients aged 20–35 years with BMI 18.5–30 kg/m², along with 90 age and BMI-matched controls. PCOS diagnosis was based on the Rotterdam criteria, and thyroid function tests (T3, T4, TSH, anti-TPO antibodies), lipid profile, and insulin resistance markers (fasting insulin, HOMA-IR) were measured. Statistical analysis was conducted with significance set at p < 0.05. The results revealed significant differences between PCOS cases and controls in waist circumference, systolic and diastolic blood pressure, T3, T4, TSH, anti-TPO levels, and lipid profile components (TG, HDL, LDL). Insulin resistance markers (fasting insulin, HOMA-IR) were also markedly higher in the PCOS group. The study highlights a strong association between PCOS and thyroid dysfunction, particularly autoimmune thyroid disease, as well as insulin resistance and dyslipidemia, suggesting that routine screening for thyroid and metabolic abnormalities in PCOS patients may be beneficial for early intervention and improved long-term outcomes.